A conceptual framework of strategy, action and performance dimensions of organisational agility development. Issue 7 (3rd July 2021) - Margherita, Alessandro; Sharifi, Hossein; Caforio, Antonio
ABSTRACT: Agility is today a key dimension of organisational excellence as it encompasses the aptitude to successfully respond to changes in the surrounding environment. Although existing research has investigated specific perspectives of organisational agility, an integrative framework is yet to be introduced in literature. This article aims to address this gap by presenting a conceptual model that encapsulates various dimensions critical to the development of agility within organisations. An extended review of literature is used to identify agility-related concepts, and a design science approach is adopted to build the framework. Three macro-areas are described in terms of 7 propositions and dimensions and 30 items concerned with an agility development initiative. The main value of the article is to provide a holistic view of agility and a number of interdisciplinary perspectives into a single representation framework. The model can also support managers involved into the execution of agility development initiatives.